Adjunctive IV tranexamic acid versus topical tranexamic acid application of the placental bed for prevention of postpartum hemorrhage in women with placenta previa: a randomized controlled trial - Shady, Nahla W.; Sallam, Hany F. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Placenta previa one of the famous etiology of excessive blood loss during and after cesarean section. The objective of this study was to determine the effect of prophylactic adjunctive IV versus topical tranexamic acid (TA) on calculated and measured blood loss during and after caesarean section due to placenta previa compared with standard IV oxytocin alone. Methods: In this double-blind randomized controlled trial, 120 women were undergoing caesarean delivery for placenta previa (PP) were randomly allocated to receive 10 IU oxytocin IV after placental delivery, or receive 1 gm tranexamic acid IV just before skin incision plus 10 IU oxytocin IV after placental delivery or received 10 IU oxytocin IV after placental delivery plus 2 gm topical tranexamic acid applied on placental bed. The main outcome was to measure blood loss during and 4-hour post caesarean delivery. Results: 120 women were enrolled (n = 40 in each group). Both groups of women received IV tranexamic acid (Group II) and topical tranexamic acid (Group III) showed great reduction in intraoperative and 4 hours post-operative blood loss compared with (Group I) which received 10 IU oxytocin only (P = 0.0001, 0.0001, 0.0001, 0.0001), so the overall estimated blood loss in group II and III showed highly reduction compared with group I (P = 0.0001, 0.0001). Conclusions: Prophylactic adjunctive TA topical application on the placental bed or iv administration reduces blood loss during and after caesarean delivery in women with a placenta previa. novel application of topical tranexamic acid on the placental bed is effective in reduce intraoperative and postoperative bleeding in comparison with IV route with elimination of theoretical risk of thrombi embolism complication with IV rout.